Perancangan Baru Hotel Butik Di Kota Bogor Dengan Pendekatan Biophilic - Destia Fitri Rahmini, Nanda; Nur Hadiansyah, Mahendra; Zulfia, Irwana (Telkom University, 2024)
Bogor City is a city known as a center for business, transportation, and tourism. One of the cities in Bogor that is a tourist destination with strategic potential for recreational tourism, staycations, and business is Sentul City, a city area that implements green city development with integration between nature, and the area provides a positive correlation with good health both mentally and physically, and is one of the cities in Indonesia that provides real access to nature. The significant growth in the number of tourists shows the need for adequate accommodation facilities to meet the needs of tourism accommodation. Therefore, with the presence of a 4-star Boutique Hotel with facilities according to user needs. Located on Jl. MH. Thamrin, this hotel targets tourists and business people. This design aims to create a 4-star boutique hotel with an attractive identity and has its own characteristics. The design of this hotel focuses on visitor comfort and meets hotel standards and the biophilic approach is emphasized to strengthen the design that describes the Sentul City area. The design methods used include data collection through literature studies, observations, and comparative studies with similar hotels. It is hoped that this design can provide benefits to the community, community, and educational institutions, and the field of interior science. This hotel is expected to be an attractive accommodation facility for tourists coming to Bogor City. Keywords: Bogor City, Sentul City, hotel, biophilic